From denunciation to commitment: are revolutionary principles for behaviorists? (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Revolutionary principles can guide analysis and actions that are potentially effective in the struggle for social justice. In that sense, we note that not only behavioral principles are for revolutionaries, as James Holland points out, but also that revolutionary principles are for behaviorists. This article aims to validate this premise, which points to the permanent need of the ethical and political debate on the consequences that guide scientific and professional practices of behavior analysts. Therefore, we analyze the meaning of “revolution” to Holland, in order to situate his speech in the political debate; we point to some political and economic bases of current life conditions; and finally we present a contemporary and revolutionary social movement called Deep Green Resistance, considering its compatibility with some concepts of the radical behaviorist philosophy.
Keywords: revolution; behaviorism; behavioral analysis of culture; anticapitalism